2012
DOI: 10.4172/2153-2435.1000175
|View full text |Cite
|
Sign up to set email alerts
|

Stability Indicating HPLC Method for Simultaneous Determination of Several Angiotensin-II-Receptor Antagonists in Their Dosage Forms

Abstract: A stability-indicating reversed-phase liquid chromatographic (RP-HPLC) method has been established for simultaneous determination of four angiotensin-II-receptor antagonists (Losartan potassium, Valsartan, Telmisartan and Irbesartan) in the presence of the degradation products generated in studies of forced decomposition. All drug substances were subjected to drastic condition of stress studies involving hydrolysis by acid and base, thermal decomposition by heat at 70°C, oxidation by hydrogen peroxide and phot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Stress conditions involve acidic and basic hydrolysis, oxidation, exposure to UV light, and exposure to temperature (dry heat). However, from a literature survey it was evident that many stability‐indicating HPLC methods are designed for the determination of atorvastatin, irbesartan, and amlodipine, separately . Interestingly, one ultrahigh performance liquid chromatography (UPLC) method was reported on the combined determination of atorvastatin, amlodipine, and irbesartan with hydrochlorothiazide, but the authors worked with single dose of each compound and the method lacked the stability‐indicating nature…”
Section: Introductionsupporting
confidence: 92%
See 3 more Smart Citations
“…Stress conditions involve acidic and basic hydrolysis, oxidation, exposure to UV light, and exposure to temperature (dry heat). However, from a literature survey it was evident that many stability‐indicating HPLC methods are designed for the determination of atorvastatin, irbesartan, and amlodipine, separately . Interestingly, one ultrahigh performance liquid chromatography (UPLC) method was reported on the combined determination of atorvastatin, amlodipine, and irbesartan with hydrochlorothiazide, but the authors worked with single dose of each compound and the method lacked the stability‐indicating nature…”
Section: Introductionsupporting
confidence: 92%
“…Irbesartan was found to be less stable to acid and alkaline hydrolysis (Figure ), resulting in 55% and 45% decomposition, respectively. It was also reported that irbesartan hydrolyzed by the breakage of the amide link in 1,3‐diazaspiro [4.4] non‐1‐en‐4‐one, which was identified as ((1‐(1‐((2 ( E ‐(1 H ‐tetrazol‐5‐yl) biphenyl‐4‐yl) methyl amino) pentylidene amino)cyclopentane carboxylic acid)) . Acidic hydrolysis results of amlodipine showed no change; therefore it can be concluded that it is stable in this condition.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Losartan potassium (Losartan) extemporaneous oral suspensions were prepared by the method used in Children’s Health Ireland at Crumlin, Ireland (method A) and as per published monographs [ 10 , 11 ] (method B), without and with addition of water, respectively. Losartan (as losartan potassium) concentration was measured over 28 days, using UV spectroscopy and a stability indicating HPLC method [ 15 , 16 ]. Suspensions were monitored for changes in pH, colour, odour and re-dispersibility.…”
Section: Introductionmentioning
confidence: 99%